2016
DOI: 10.1038/srep25157
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of coherent transport

Abstract: Coherent transport phenomena are difficult to observe due to several sources of decoherence. For instance, in the electronic transport through quantum devices the thermal smearing and dephasing, the latter induced by inelastic scattering by phonons or impurities, destroy phase coherence. In other wave systems, the temperature and dephasing may not destroy the coherence and can then be used to observe the underlying wave behaviour of the coherent phenomena. Here, we observe coherent transmission of mechanical w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The structured elastic systems reported here can be easily generalized to more complex quantum systems in 2D or 3D, such as molecules graphene, graphene nanoribbons with an electric field 34 (changing the site size to emulate electric fields 33 ), among many others. Transport through molecular junctions can also be implemented using the techniques recently developed by our group 35 . For obvious reasons, with the advantages and challenges of the macroscopic systems used, this gives the possibility of analyzing problems that cannot be studied easily in atomic systems due to experimental limitations.…”
mentioning
confidence: 99%
“…The structured elastic systems reported here can be easily generalized to more complex quantum systems in 2D or 3D, such as molecules graphene, graphene nanoribbons with an electric field 34 (changing the site size to emulate electric fields 33 ), among many others. Transport through molecular junctions can also be implemented using the techniques recently developed by our group 35 . For obvious reasons, with the advantages and challenges of the macroscopic systems used, this gives the possibility of analyzing problems that cannot be studied easily in atomic systems due to experimental limitations.…”
mentioning
confidence: 99%
“…By testing different heuristic transition models between Poisson and the Gaussian orthogonal ensemble (GOE), it is shown that the Rosenzweig-Porter model best fits the numerical results. Furthermore wave amplitudes, whose eigenvalues are involved in the avoided crossing, are measured experimentally using acoustic resonant spectroscopy, a technique which has been successfully applied to study bending vibrations on integrable and chaotic plates [33,34]. As expected, the vibrational modes exchange their identities as they pass through the avoided crossing.…”
Section: Introductionmentioning
confidence: 81%
“…Thus, in what follows, measurements that prove the existence of avoided crossings for three of the four symmetry classes are reported. A generalization of the resonant acoustic spectroscopy technique [34,53] was used to verify the shape of the predicted stationary patterns "before" and "after" an avoided crossing. Three aluminum plates with identical mechanical properties were used in the experiments, with a width of 355 mm, thickness of 6.35 mm, and lengths of 400, 500, and 800 mm.…”
Section: Rmt Transition Models Fits For the Distribution Of The Ratio...mentioning
confidence: 99%

Deviations from Poisson statistics in the spectra of free rectangular thin plates

López-González,
Franco-Villafañe,
Méndez-Sánchez
et al. 2021
Preprint
Self Cite
“…For instance, Landauer formula states that the electrical conductance is proportional to the transmission coefficient [6]; an equivalent Landauer formula is valid for thermal conductance [7]. Therefore, a lot of research has been devoted to the study of conduction through twoterminal configurations from the theoretical and experimental points of view, using quantum mechanics [8][9][10][11][12] as well as classical wave physics [2,3,13,14].…”
Section: Introductionmentioning
confidence: 99%